Observation of Hydrogen-Induced Dzyaloshinskii-Moriya Interaction and Reversible Switching of Magnetic Chirality - Gong Chen (American Physical Society, 2021)
The Dzyaloshinskii-Moriya interaction (DMI) has drawn much attention, as it stabilizes magnetic chirality, with important implications in fundamental and applied research. This antisymmetric exchange interaction is induced by the broken inversion symmetry at interfaces or in noncentrosymmetric lattices. Significant interfacial DMIs are often found at magnetic/heavy-metal interfaces with large spin-orbit coupling. Recent studies have shown promise for induced DMI at interfaces involving light elements such as carbon (graphene) or oxygen. Here, we report direct observation of induced DMI by chemisorption of the lightest element, hydrogen, on a ferromagnetic layer at room temperature, which is supported by density functional theory calculations. We further demonstrate a reversible chirality transition of the magnetic domain walls due to the induced DMI via hydrogen chemisorption and desorption. These results shed new light on the understanding of DMI in low atomic number materials and the design of novel chiral spintronics and magneto-ionic devices.